Massal selection of acerola in commercial orchard - de Paiva, João Rodrigues; Alves, Ricardo Elesbão; Correa, Maria Pinheiro Fernandes; Freire, Francisco das Chagas Oliveira; Sobrinho, Raimundo Braga (Pesquisa Agropecuaria Brasileira, 1999)
Genetic variability can easily be found in commercial orchards allowing the selection of superior matrix plants. The main purpose of this work was to conduct a selection of acerola (Malpighia emarginata) plants in the Frutas do Ceará S/A (FRUCESA) orchard, in Jaguaruana county, CE, Brazil. The mass selection allowed the choice of 100 desirable plants. Seed germination varied from 0.0% to 84.5%, mean of 13.9% and standard deviation of 11.6%, suggesting the occurrence of genetic variation among plants for this character.